The Impact of Technological Support, Digital Green Innovation, and Information Management Integration on Business Sustainability - Calvin Ryandra; Vinsensius Vinsensius; Joni Riawan; Dyson Jonathan (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
Digital transformation in business operations has been spurred by the increasing worldwide awareness of environmental concerns. This includes micro, small, and medium businesses (MSMEs) in Indonesia's food and beverage sector. The purpose of this research is to analyze how digital green innovation, information management integration, and technical assistance affect the long-term viability of companies. In this study, 90 MSMEs were chosen using a purposive sample method, and a quantitative approach was used with a cross-sectional design. A 5-point Likert scale questionnaire was used to collect data, which was then analyzed in SPSS using multiple linear regression. The results show that, simultaneously, all three independent variables significantly affect business sustainability. However, partially, only information management integration and digital green innovation show significant influence, while technological support does not have a direct significant effect. These findings emphasize that technology must be strategically aligned with innovation and integrated information systems. Theoretically, the study supports the Resource-Based View approach, highlighting internal resources as the foundation of sustainable competitive advantage. Practically, MSMEs are encouraged to enhance information integration and digital green innovation as part of their digital transformation strategy to strengthen competitiveness and achieve long-term sustainability.